Assessment of three-dimensional joint kinematics of the upper limb during simulated swimming using wearable inertial-magnetic measurement units - Fantozzi, S.; Giovanardi, A.; Magalhães, F. A.; Di Michele, R.; Cortesi, M.; Gatta, G. (Journal of Sports Sciences, 2016)
The analysis of the joint kinematics during swimming plays a fundamental role both in sports conditioning and in clinical contexts. Contrary to the traditional video analysis, wearable inertial-magnetic measurements units (IMMUs) allow to analyse both the underwater and aerial phases of the swimming stroke over the whole length of the swimming pool. Furthermore, the rapid calibration and short data processing required by IMMUs provide coaches and athletes with an immediate feedback on swimming kinematics during training. This study aimed to develop a protocol to assess the three-dimensional kinematics of the upper limbs during swimming using IMMUs. Kinematics were evaluated during simulated dry-land swimming trials performed in the laboratory by eight swimmers. A stereo-photogrammetric system was used as the gold standard. The results showed high coefficient of multiple correlation (CMC) values, with median (first-third quartile) of 0.97 (0.93-0.95) and 0.99 (0.97-0.99) for simulated front-crawl and breaststroke, respectively. Furthermore, the joint angles were estimated with an accuracy increasing from distal to proximal joints, with wrist indices showing median CMC values always higher than 0.90. The present findings represent an important step towards the practical use of technology based on IMMUs for the kinematic analysis of swimming in applied contexts.